The Concept Attainment Learning Model In Improving Understanding Of Mathematics Concepts In Primary Schools - Mira Helpiana; Rusdial Marta; Yenni Fitra Surya; Fadhilaturrahmi Fadhilaturrahmi; Nurhaswinda Nurhaswinda (Universitas Muhammadiyah Enrekang, 2023)
This research was motivated by the low understanding of Mathematics concepts in class III students at SDN 004 Salo. This is because the learning model has not been able to improve students' understanding of Mathematics concepts in the learning process. One solution to overcome this problem is to apply the Concept Attainment learning model . This research aims to describe increasing students' understanding of Mathematics concepts by applying the Concept Attainment learning model for class III students at SDN 004 Salo. This research method is classroom action research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementation, observation and reflection. The research subjects were 20 class III students. Data collection techniques include interview techniques, observation, tests and documentation. Based on the results of data analysis, it can be seen that there was an increase in students' results of Understanding Mathematical Concepts before the action, the average completeness of students' Understanding of Mathematical Concepts results was only 25% with classical completeness of 59%, then in the first cycle of the first meeting it increased to 35% with classical completeness of 65. 25%, then in cycle I, meeting II increased to 50% with classical completeness of 71.5%. Furthermore, cycle II, meeting I increased to 65% with classical completeness of 73% and cycle II, meeting II increased to 80% with classical completeness of 80.5%. So it can be concluded that the application of the Concept Attainment Learning model can improve the understanding of Mathematics concepts for class III students at SDN 004 Salo. Keywords: Concept Attainment Learning Model , Understanding Mathematical Concepts, Elementary School